The Role of Digital-Based Leadership in Developing Schools in the Era of Industrial Revolution 4.0 - Prestiadi, Dedi; Nurabadi, Ahmad (Journal of Education for Sustainability and Diversity, 2025)
The purpose of writing this article is to find out the role of digital-based leadership in the development of schools in the era of the Industrial Revolution 4.0. The Industrial Revolution 4.0 is characterized by rapid technological advances and the penetration of digitalization in various sectors, including education. Digital-based leadership refers to the ability of leaders to utilize digital technology in managing and advancing educational institutions. In this context, school leaders are required to master information and communication technology, implement digital management systems, and create an innovative and responsive learning environment for technological changes. The research method used is a literature study to find out descriptively how digital-based leadership can improve the quality of education in the Industrial Revolution Era 4.0. The results of this study show that digital-based leadership is the key to creating schools that are adaptive and competitive in the digital era.